Hubungan Yesus Kepada Tuhan Dan Solidaritas Dengan Anak-Anak Dalam Ibrani 2:13: Memahami Penggunaan Perjanjian Lama Dalam Perjanjian Baru (Jurnal Pendidikan Agama dan Teologi, 2023)
The New Testament is the main source in understanding Christology which is the science of theology that talks about Christ the Messiah. Talking about Christology, the letter to Hebrews has the highest Christology. In Hebrews 2:13 the author understands it as "Jesus' relationship to the Father and his solidarity with the children" which is the result of a quote from the OT in Isaiah 8:17-18. However, this has given rise to much debate. How could the author of Hebrews understand Isaiah 8:17-18 as the relationship between Jesus to the Father and his solidarity with the children who have been given to Him, while there clearly talks about the life of the prophet Isaiah and his children who still choose to cling to God even though they are in the midst of an unbelieving nation. For this reason, in interpreting Hebrews 2:13 we use an approach using steps of interpretation (understanding the use of the Old Testament into the New Testament).